ANALISIS PERAMALAN (FORECASTING) PENJUALAN IKAN NILA DENGAN MENGGUNAKAN METODE LINIER REGRESSION - Maria Tirsa Daber; Heru Sutejo, Irma Pamantin, Carmenita Mori, Stevania Jowey, Novita Merne, Trivena Dimara (CV. ADIBA AISHA AMIRA, 2026)
This study aims to forecast tilapia sales in Nendali Village, Sentani, Papua using the Linear Regression method. The problem addressed is the fluctuation of production and sales, which requires a method to predict future sales. This research uses a quantitative method with a descriptive approach based on tilapia sales data from January 2024 to December 2025, including harvest quantity, price per kilogram, and total salesThe analysis applies linear regression to determine the relationship between time (X) and harvest quantity (Y). The results produce the regression equation Y = 350.44 + 4.565X, indicating an increase in tilapia production of 4.565 Kg per month. The forecasting results for 2026 show an increase from 464.56 Kg in January 2026 to 514.79 Kg in December 2026. Model accuracy is evaluated using MAD, MSE, and MAPE. The results indicate that the linear regression method can be used as a tool to support tilapia production planning and sales management.